KOMUNIKASI INTERPERSONAL ANTARA GURU DENGAN SISWA KELAS VIA DALAM MENANGANI KENAKALAN SISWA (STUDI KASUS SDN KEPUTIH 245 SURABAYA) - Susanti, Susanti; Sudaryanto, Edy; Nasution, Ute Chairus (Universitas 17 Agustus 1945 Surabaya, 2018)
This research aims to find out the communication process between teacher andstudent in handling student misbehavior involving homeroom teacher, one other teacher,and ten students of VI A class who often misbehave. Using the interpersonalcommunication theory of Devito, this researcher collects the data through observation,deep interview, and documentation study. This research results that the interpersonalcommunication between teacher and student has effectively worked. However, there aresome barriers experienced by teachers particularly when students are afraid of facingtheir teacher. Therefore, they tend to be less open to their teacher. Besides, seen from theempathy, teachers and students have supportive and positive attitude and good equality.It is concluded that the interpersonal communication between teacher and student in SDNKeputih 245 Surabaya has effectively worked. This interpersonal communication canlead to increase the interpersonal relationship between teacher and student.Key words: interpersonal communication, student misbehavior, handling studentmisbehavior, effective interpersonal communication.